2013
DOI: 10.1039/c3cy00007a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dye dispersion on photoelectric conversion properties of dye-containing titania electrodes

Abstract: The dye-dispersing titania electrodes were prepared from the dye-containing titanium alkoxide sols by a room temperature sol−gel process and steam treatment at 110°C. The spectroscopic and photoelectric conversion properties of the electrodes were investigated in order to clarify the influences of the dye dispersion and the co-dispersion of the two dyes on the electron transfer process. The fluorescein and eosin Y molecules were dispersed into the titania as their monomers. The shapes of the photocurrent actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
(125 reference statements)
3
13
0
Order By: Relevance
“…The IPCE values of the dye-dispersing electrodes were higher than those of the dye-adsorbing electrodes due to their strong interaction between the dye and titania as previously reported (Nishikiori et al, 2011c(Nishikiori et al, , 2013b. This result indicated that allophane decreased the electronic conductivity of the electrode causing the back electron transfer.…”
Section: Photoelectric Conversion Properties Of the Electrodessupporting
confidence: 59%
“…The IPCE values of the dye-dispersing electrodes were higher than those of the dye-adsorbing electrodes due to their strong interaction between the dye and titania as previously reported (Nishikiori et al, 2011c(Nishikiori et al, , 2013b. This result indicated that allophane decreased the electronic conductivity of the electrode causing the back electron transfer.…”
Section: Photoelectric Conversion Properties Of the Electrodessupporting
confidence: 59%
“…In a further study, the steam treatment enhanced the photoelectric conversion efficiency of the fluorescein‐dispersing titania gel due to not only crystallization of the titania gel but also the dye–titania surface complex formation . Based on the results of the time‐resolved spectroscopy and photoelectric measurements, the electron injection process from the dye‐excited states to the titania conduction band is important for the photoelectric conversion.…”
Section: Introductionmentioning
confidence: 96%
“…The compounds in such materials exhibit a more efficient light harvesting and fluorescence because they are finely dispersed in the amorphous or nanosized crystalline matrices compared to the conventional dye-adsorbing materials [20][21][22][23]. Therefore, it is expected that such films exhibit a higher function, stability, and performance in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthene dyes as laser dyes are available materials for utilizing photoenergy due to their high absorption and fluorescence efficiencies in various visible light regions [32]. It was reported that the hydrothermal treatment of a dye-dispersing amorphous titania film remarkably improved the photoelectric conversion efficiency due to not only its crystallization but also the dye-titanium complex formation [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation